Oxygen-Generating Photocrosslinkable Hydrogel - ALEMDAR YAYLA, NESLİHAN (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
Providing sufficient amount of oxygen to the cells is a critical issue since the lack of adequate oxygen leads to cell death and tissue necrosis. Therefore, there is a vital need to design and fabricate oxygen-generating biomaterials to mitigate hypoxia-induced cell death in engineered tissues. Here, we report the fabrication of an oxygen-generating hydrogel by incorporating calcium peroxide (CPO) into the methacrylated gelatin (GelMA) structure using photocrosslinking process. A sustainable release of oxygen could be provided from CPO-GelMA hydrogel over a period of 5 days under hypoxic conditions (1% O-2).
Keywords: Gelatin; Photocrosslinking; Oxygen-generating hydrogel; TISSUE; GELATIN; SCAFFOLDS